Participatory rural appraisal of local communities of the south-east Pahang peat swamp forest: grassroots involvement in peat swamp forest conservation / Gill, S.K. and Khali A.H. - S.K., Gill; A.H., Khali (2006)
Environmental problems are a common concern, the solution of which requires the active and responsible involvement Of different stakeholders, especially people at the grassroots level who are most susceptible to changes in their natural environment. Indigenous communities in many parts of the world are seldom consulted on issues pertaining to rural development and conservation. They often bore the brunt of many ill-thought-out policies which contributed further to their marginalization. Learning from past mistakes and acknowledging the vital role of indigenous peoples in determining policies for their own socio-economic development, the UNDP/GEF funded Peat Swamp Forest (PSF) Project recognised the need for a paradigm shift toward a more participatory approach in the ongoing conservation efforts in the South-East Pahang Peat Swamp Forest (SEPPSF) involving the indigenous Asli Jakun community. The methodology adopted was the bottom-up Participatory Rural Appraisal (PRA) technique which is widely used in developing countries as a tool to encourage local participation, gauge perceptions and learn from local people about their concerns and desires for a more sustainable future. This paper highlights the strategy adopted, outcomes and lessons learnt in the PRA study with respect to the sustainable use of PSF resources by the Asli Jakun in three villages in the SEPPSF.